THE ISOLATION RATES OF VAGINAL GROUP B STREPTOCOCCI AMONG NON-PREGNANT, PREGNANT AND DIABETIC WOMEN AND THEIR ANTIMICROBIAL SUSCEPTIBLITY - Tevfik, Mehmet Refik; Mehmet, Nihayet; Dizaii, Ziyan Mahmut (Fırat University, 2001)
Objective: To determine the isolation rates and antimicrobial susceptibility of vaginal group B streptococci (GBS) in non-pregnant, pregnant and diabetic women. Material and Method: Vaginal cultures were made from 280 women attending gynaecological outpatient unit of Erbil Obstetrics and Gynaecology Hospital. Of these, 90 were non-pregnant 128, pregnant and 62 diabetic women. Antimicrobial susceptibilty test was made. Results: The numbers and isolation rates of group B Streptococcus were found to be 2(2.2 %) non-pregnant, 6(% 4.6) pregnant and 9(4.5 %) diabetic women. There was statistically no significant difference between pregnant and non-pregnant women (P>0.05), while significant difference was seen between non-pregnant and diabetic women (P

Amaç: Gebe olan, gebe olmayan ve diabetik kadınlarda vajinal grup B streptokokların (GBS) izolasyon oranı ve antimikrobiyal duyarlıklarının saptanması. Gereç ve yöntem: Erbil Kadın Doğum Hastanesi Jinekoloji polikliğine başvuran 280 kadın hastadan vajinal kültürler alındı. Bunların 128'i gebe 90'ni gebe olmayan ve 62'si diabetik kadınlardı. Antimikrobiyal duyarlık testi yapıldı. Bulgular: Grup B streptokok sayıları ve izolasyon oranı sırası ile gebe olmayanlarda 2 (%2.2), gebelerde 6 (%4.6) ve diabetik kadınlarda 9 (%4.5) olarak bulundu. Gebe olanlar ile olmayanlar arasında istatistiksel olarak anlamlı fark yok iken gebe olmayanlar ile diabetik kadınlar arasında anlamlı fark görüldü (P
GEBE OLMAYAN GEBE ve DİYABETİK KADINLARDA GRUP B STREPTOKOK İZALASYON ORANLARI ve ANTİMİKROBİYAL DUYARLILIKLARI